2018
DOI: 10.1177/0885066618769021
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Supporting Clinical Use of Proportional Assist Ventilation: A Systematic Review and Meta-Analysis of Clinical Trials

Abstract: Current evidence does not support the use of invasive or noninvasive PAV or invasive PAV+ in critically ill adults. Amid low to moderate heterogeneity, we identified 3 promising areas for future research including assessing the role of noninvasive PAV as an initial support strategy in patients with acute respiratory failure, invasive PAV on sleep quality during invasive ventilation, and possibly invasive PAV+ for weaning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
15
1
2
Order By: Relevance
“…The red line in a triangle shape represents the futility boundaries and futility area in TSA. In this figure, TSA of the primary outcome, weaning success, showed that the Z-curve has not yet reached the required information size, but crosses the conventional boundary and the trial sequential monitoring boundary curve for benefit with statistical significance, suggesting conclusive and robust results in favor of PAV reducing the length of ICU and hospital stay [8]. This study investigated the efficacy of PAV as a weaning mode, compared to PSV.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The red line in a triangle shape represents the futility boundaries and futility area in TSA. In this figure, TSA of the primary outcome, weaning success, showed that the Z-curve has not yet reached the required information size, but crosses the conventional boundary and the trial sequential monitoring boundary curve for benefit with statistical significance, suggesting conclusive and robust results in favor of PAV reducing the length of ICU and hospital stay [8]. This study investigated the efficacy of PAV as a weaning mode, compared to PSV.…”
Section: Discussionmentioning
confidence: 96%
“…We also performed trial sequential analysis to reduce both type 1 and type 2 errors, avoiding overestimates, and consolidating our result. In another meta-analysis [8], the evidence supporting clinical use of PAV as a weaning modality was assessed. The authors found that PAV resulted in an insignificant reduction in weaning time and had no effect on mortality reduction or reintubation rate compared to PSV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little clarity regarding the best strategy to use to liberate patients who fail multiple SBTs. Although PS is the most common mode used worldwide at this stage of mechanical ventilation, clinicians may use multiple other modes of partial ventilator assist such as synchronised intermittent mandatory ventilation (SIMV), continuous positive airway pressure (CPAP), adaptive support ventilation (ASV), airway pressure release ventilation (APRV), proportional assist ventilation (PAV) or neutrally adjusted ventilator assist (NAVA) 10–14…”
Section: Introductionmentioning
confidence: 99%
“…Prior systematic reviews and meta-analyses examining this question have combined heterogeneous interventions to allow for pairwise comparisons resulting in estimates of effect that are difficult to interpret 16–18. Moreover, the advent of newer weaning techniques, such as PAV with load-adjustable gain factors (PAV+), NAVA or Intellivent and SmartCare, mandates assessment of the comparative efficacy of these newer techniques 11–14Table 1 summarises some of the ventilatory modes that have been used for gradual weaning.…”
Section: Introductionmentioning
confidence: 99%